The Cosmic Keyhole How Astronomy Is Unlocking the Secrets of the Universe - Gater, William J.H. (Astronomers' Universe, 2009)
It is 400 years since Galileo first turned the newly invented telescope towards the heavens and saw things that few had ever seen before. His discoveries, along with those of his contemporaries, completely changed our view of the world. Since that time, there have been many revolutions in our understanding of the universe, some perhaps even more revolutionary than the ones from Galileos time. In this book, Will Gater leads us through various recent advances in modern astronomy that have increased our understanding of the universe and seen it grow from a single Solar System full of intriguing worlds to a galaxy filled with other star systems and their own planets maybe even Earthlike worlds. This is a journey like no other. What you glimpse through Gaters keyhole is vast, breathtakingly beautiful, and sometimes utterly bizarre, certainly unfamiliar to those of us on Terra Firma. From the desolate plains of Mars and the frozen moons of the outer Solar System, from the Milky Way to the ends of the universe, you will learn of wonders often hard to describe and sometimes even harder to fathom. And you, too, will come to know some of the enthralling secrets of the universe.